One-step additive crosslinking of conjugated polyelectrolyte interlayers: improved lifetime and performance of solution-processed OLEDs. Issue 47 (14th November 2016) - Stolz, Sebastian; Petzoldt, Martin; Kotadiya, Naresh; Rödlmeier, Tobias; Eckstein, Ralph; Freudenberg, Jan; Bunz, Uwe H. F.; Lemmer, Uli; Mankel, Eric; Hamburger, Manuel; Hernandez-Sosa, Gerardo
Abstract : We crosslink an amino-functionalized polyfluorene by the solvent additive 1, 8-diiodooctane (DIO). Abstract : We crosslink an amino-functionalized polyfluorene by the solvent additive 1, 8-diiodooctane (DIO). DIO remains in the film after drying of the main solvent and chemically binds to the amino-side groups after a low temperature annealing step, rendering the polyfluorene film insoluble in non-polar solvents. We correlate the amount of DIO, the reduction of operational voltage and increase in lifetime of solution-processed OLEDs. We demonstrate a fully solution-processed device using the crosslinked polyfluorene electron injection layer and an inkjet-printed Ag top electrode.